Impossible to Go Beyond Beef? An Unbiased Metabolomics Analysis. (29th May 2020) - Vliet, Stephan van; Bain, James; Muelbauer, Micheal; Kronberg, Scott; Provenza, Fred; Huffman, Kim; Kraus, William
Abstract: Objectives: Novel plant-based meat alternatives are becoming increasingly popular with consumers. The new generation of meat alternatives is specifically formulated to closely mimic the taste, sensory experience, and nutritional composition of meat. The goal of this work was to perform unbiased analysis of the biochemical composition of ground beef versus a novel plant-based meat alternative to determine their nutritional equivalency. Methods: Ground beef from eighteen different steers was purchased from Alderspring Ranch, ID. Eighteen different packages of a plant-based meat alternative were purchased from a local grocery store. Non-targeted metabolomic analysis of sample homogenates was conducted via gas chromatography/electron-ionization mass spectrometry (GC/ei-MS) in the Metabolomics Laboratory of the Duke Molecular Physiology Institute. Following log-transformation, t-test were used to compare all individual analytes using a p-value (false discovery rate) cutoff of P  < 0.01, without adjustment for multiple comparisons. Multivariate analyses (principal component and cluster analysis) was performed using software procedures in MetaboAnalyst 4.0. Results: A total of 159 out of 184 detected metabolites were found to be different between beef and the plant-based meat alternative ( P  < 0.01). Metabolites such as niacinamide, calcium pantothenate, creatinine/creatine, anserine, hydroxyproline, and glucosamine were only found in beef, while metabolites such as delta-tocopherol, 3-hydroxyanthranilic acid, vanillic acid, and various plant sterols were only found in the plant-based alternative. Conclusions: Despite suggested similarity based on their Nutrition Facts panel, we show that metabolites with important regulatory roles in human health are either absent or present in lower quantities in the plant-based meat alternative. These data suggest that novel plant-based meat alternatives should, at present, not be viewed as direct nutritional replacements for red meat. Funding Sources: None.